1984 A camptown story. (2nd September 2017) - Lee, Jung Joon
Abstract : This essay examines Kim Yongt'ae's photocollage DMZ, which consists of photo-portraits he acquired from commercial photo studios in US military camptowns in South Korea. The co-founding member of the South Korean artist group Hyŏnsilgwa parŏn (Reality and Utterance), Kim visited camptowns in 1984. There, he found hundreds of studio photo-portraits depicting Korean women and American GIs serving United States Forces Korea (USFK). While discussions on "found" photographs often center on the discourses of archive, appropriation, or vernacularity appended by the cultural specificity of their origins, this essay proposes a new framework through which Kim's work is explored: transnational militarism and "disidentification" — a concept put forth by José Esteban Muñoz on minoritarian performativity. Through this framework, DMZ challenges the binary reading of camptown subjects as victim and victimizer and proposes the performative formation of a new subjectivity.